PENGEMBANGAN MEDIA INTERAKTIF “ABAYA” AYO BELAJAR BUDAYA BERBASIS CANVA UNTUK MENINGKATKAN MINAT BELAJAR IPAS SISWA SDN 2 PADOKAN BANTUL : Penelitian Pengembangan - Nadia Endah Widyaningrum; Urip Muhayat Wiji Wahyudi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to develop ABAYA (Ayo Belajar Budaya), an interactive learning media based on Canva to improve fourth-grade students’ interest in IPAS learning at SDN 2 Padokan. The development used the ADDIE model through five stages: analysis, design, development, implementation, and evaluation. The media was validated by experts and tested in both limited and field trials. Student and teacher responses showed high practicality (89% and 97% respectively). The effectiveness was measured through pre- and post-interest questionnaires, showing an increase from 68.4% to 86%. A paired sample t-test indicated a significant improvement (Sig. 0.000 < 0.05). The results suggest that ABAYA is feasible and effective to support IPAS learning in elementary schools.